2022
DOI: 10.1002/er.8104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of quaternary Heusler alloys CoFeYGe ( Y  = Ti, Cr) with respect to structural, electronic, magnetic, mechanical, and thermoelectric features

Abstract: The electronic, magnetic, elastic, and thermoelectric properties of CoFeYGe (Y = Ti, Cr) quaternary Heusler compounds are studied using DFT simulations. Our calculations show that both CoFeYGe (Y = Ti, Cr) alloys have a Type-I atomic configuration. CoFeCrGe and CoFeTiGe compounds with band gaps of 0.640 eV and 0.489 eV, respectively, were found to display half-metallic behavior in the minority spin channels. The total magnetic moment of CoFeCrGe was 3.00 μ B , while CoFeTiGe's was 1.00 μ B . CoFeTiGe and CoFeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Heusler alloys of both quaternary FeVScSb and FeVYSb form cubic crystals of the LiMgPdSn (Y‐type) phase (space group Ftrue4¯3m$F \bar{4} 3 m$). [ 48–52 ] This structure has three possible nonequivalent superstructures (YI, YII, and YIII) summarized in Table 1 . In both FeVScSb and FeVYSb Heuslers, the three possible nonequivalent atomic arrangements (YI, YII, and YIII) are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Heusler alloys of both quaternary FeVScSb and FeVYSb form cubic crystals of the LiMgPdSn (Y‐type) phase (space group Ftrue4¯3m$F \bar{4} 3 m$). [ 48–52 ] This structure has three possible nonequivalent superstructures (YI, YII, and YIII) summarized in Table 1 . In both FeVScSb and FeVYSb Heuslers, the three possible nonequivalent atomic arrangements (YI, YII, and YIII) are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For the practical implementation of any compounds especially in the field of TE applications; machinable factor (µ m ), Frantsevich ratio (G/B), and melting temperature (T m ) played a key role [63]. The calculated µ m by employing equation (12) suggest that the QHAs being investigated exhibit an acceptable level of machinability with lower feed forces and mediocre lubricating properties. Also, from the high T m and low G/B ratio, one can conclude that these compounds could be the next future TE materials that can be utilized at high temperatures.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Through the surveyed literature, it was found that Heusler alloys (HA) were broadly divided into four components namely; direct full-HA that crystallizes in L2 1 structure, consisting of four inter-penetrating face centered cubic (FCC) lattices with space group-225 (Fm-3m), inverse full-HA crystallizes in C1 b type structure with space group-216 (F-43m), half-HA that belongs to C1 b type structure, consisting of three in-equivalent atoms forming inter-penetrating FCC sub-lattices, and Quaternary-HA (QHA) that fits in C1 b structure with four in-equivalent atoms [3,8,9]. Over the last few decades, the theoretical and the experimental insight into novel semi-conducting QHA for TE devices have attracted much attention as they fulfill all the requisites for the materials to be utilized in the TE devices such as mechanical and thermal stability, non-toxicity, availability and the cost-effectiveness [10][11][12][13][14][15][16][17]. Also, the ease of tuning electronic properties through the band gap engineering.…”
Section: Introductionmentioning
confidence: 99%